The Effect of Soil Particles Diameter by Passing The Sieve Analysis to Soil Compaction Using The Standard Method - Salsabila, Adira; Adha, Idharmahadi; Zakaria, Ahmad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2019)
Improving the Infrastructure development needs the soil that capable to support the load. It because soil is a material that major the role to support every construction. To identify a good soil is by doing physical and mechanical soil test. Soil compaction is process of increasing the soil density by reducing the particles proximity so it can reduce the air volume. Soil type is influencing to the maximum dry volume weight and optimum water content of that soil. Based on the soil type, compaction is divided into four types. In this research is using two types of compactions that are type A and Type C with purpose to find out the effect of soil particles diameter by passing sieve analysis to soil compaction using standard method.Compaction is done based on blow method and pressure method. In pressure method is using modification compaction tool with 5 Mpa, 10 Mpa, and 15 Mpa pressures.The result of this research is the blow method compaction type A has a higher water content than type C, but the value of maximum dry volume weight Type C higher than type A.  In pressure method it can be concluded that as the higher pressure so the water content and the maximum dry volume weight are also getting higher.Keyword:Soil Particles, Standard Method of Compaction, Blow Method and Pressure Method Compaction